Design as Research : Positions, Arguments, Perspectives - Bredies, Katharina; Christensen, Michelle; Conradi, Florian; Joost, Gesche; Unteidig, Andreas (Board of International Research in Design, 2016)
Are there differences between design practice and the practice of design research? What alliances between text and artefact are possible in the search for new knowledge? How does design research translate and transform theories and methods from other disciplines? Is design research moving towards becoming a formal discipline and, if so, would this really be an advantage? 16 international authors address these four different aspects in the form of personal statements, and 19 researchers share their reflections based on their experience of having carried out a practice-based PhD. This book investigates the status quo of things in the multi-faceted and constantly evolving field of design research, and outlines the elementary issues faced by researchers. The compendium is a survey of a fast-growing field and, at the same time, provides pointers for personal orientation. With statements from: Uta Brandes, Rachel Cooper, Clive Dilnot, Michael Erlhoff, Alain Findeli, Bill Gaver, Ranulph Glanville, Matthias Held, Wolfgang Jonas, Klaus Krippendorff, Claudia Mareis, Mike Press, Elizabeth B.-N. Sanders, Arne Scheuermann, Cameron Tonkinwise, Brigitte Wolf